2016
DOI: 10.1111/pala.12273
|View full text |Cite
|
Sign up to set email alerts
|

A cryptic record of Burgess Shale‐type diversity from the early Cambrian of Baltica

Abstract: Exceptionally preserved 'Burgess Shale-type' fossil assemblages from the Cambrian of Laurentia, South China and Australia record a diverse array of non-biomineralizing organisms. During this time, the palaeocontinent Baltica was geographically isolated from these regions, and is conspicuously lacking in terms of comparable accessible early Cambrian Lagerst€ atten. Here we report a diverse assemblage of small carbonaceous fossils (SCFs) from the early Cambrian (Stage 4) File Haidar Formation of southeast Sweden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 132 publications
1
53
0
Order By: Relevance
“…3c). In contrast to sparsely fossiliferous mid-shelves, inner-and outer-shelf facies preserved most diverse SCFs assemblages, along with conspicuous burrows and bioturbation fabrics (Slater et al, 2017). These palaeontological data corroborate the geochemical signatures for oxygenated inner-and outer-shelf environments (Fig.…”
Section: Resultssupporting
confidence: 77%
“…3c). In contrast to sparsely fossiliferous mid-shelves, inner-and outer-shelf facies preserved most diverse SCFs assemblages, along with conspicuous burrows and bioturbation fabrics (Slater et al, 2017). These palaeontological data corroborate the geochemical signatures for oxygenated inner-and outer-shelf environments (Fig.…”
Section: Resultssupporting
confidence: 77%
“…The reconstructed origins of the molluscan lineage, for example, have been overhauled in order to accommodate two emblematic Cambrian taxa, Halkieria and Wiwaxia 29 . These two genera bear superficially similar sclerites, which occur the world over as carbonaceous and mineralized microfossils 1013 ; the grouping Sachitida was erected to reflect this perceived commonality 14 . The case for phylogenetic proximity was strengthened by the discovery of articulated specimens in the Burgess Shale and Sirius Passet Lagerstätten , which showed that the sclerites of both taxa were dorsal and imbricating 2,15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…This fossil bears a striking resemblance to the SCF chaetae Baltichaeta jormunganda known from younger deposits of the early Cambrian Stage 4 File Haidar Formation of Sweden (compare with Slater et al . , fig. 8, in particular specimen 8E).…”
Section: Small Carbonaceous Fossilsmentioning
confidence: 99%
“…On Baltica, sediments preserving a rich record of SCFs have been discovered from the early Cambrian of Sweden (Slater et al . ; Guilbaud et al . ; Kesidis et al .…”
mentioning
confidence: 99%